The Relationship Between Knowledge and Attitude of Women of Fertile Age Towards Preconception Screening in Preparation for Pregnancy at UPTD Paconkang Community Health Center, Soppeng District - Sahidah; Nurdin, Nasrayanti; Jaya, Fitri (INDOGENIUS, 2025)
Background & Objective: Preconception care is a service aimed at identifying factors related to health issues, lifestyle habits, or unfavorable social problems that may affect pregnancy. Method: The type and method of research used in this study is quantitative analytic research with a Cross-Sectional Study approach, which is a type of study used to examine the relationship between independent variables (knowledge and attitudes of women of childbearing age) and the dependent variable (preconception screening) at the same time the study is conducted. The population in this study consisted of all married women of childbearing age who underwent screening at UPTD Pacongkang Health Center, Soppeng Regency, totaling 30 participants. The sampling method used in this study was Purposive Sampling, which is a deliberate sampling technique based on specific criteria or considerations. Result: Based on the Chi-square statistical test, the results showed that p-value = 0.715 > α = 0.05, indicating that H0 was accepted and Ha was rejected. Conclusion: Thus, it can be concluded that there is no significant relationship between the knowledge of women of childbearing age and preconception screening in pregnancy preparation at Pacongkang Health Center. Furthermore, the Chi-square statistical test also resulted in a p-value = 0.456 > α = 0.05, indicating that H0 was accepted and Ha was rejected. This means that there is no significant relationship between the attitudes of women of childbearing age and preconception screening in pregnancy preparation at Pacongkang Health Center.